Responses of Sulfur, Nitrogen and Irrigation Water on Zea Mays Growth and Nutrients Uptake - Rahman, M.M.; Soaud, A.A.; Darwish, F.H.A.; Sofian-Azirun, Mohd (2011)
Availability of both native and applied nutrients is one of the major constrains for plants growth in sandy calcareous soils. Elemental sulfur (S 0) is often applied to acidify calcareous soil which increases the availability of nutrients in soils. The present study was sought to examine the effect of S 0 combined with or without N under acidified (pH 6.5) and normal (pH >7.5) irrigation water on growth, apparent N-use efficiency (NUE) and uptake availability of nitrogen (N), phosphorus (P), sulfur (S), iron (Fe), zinc (Zn) and manganese (Mn) by corn plants grown in calcareous soils. Elemental S at rates of 0, 1, 5 and 10 t ha -1 were tested combined with or without N at rates of 0 and 0.34 t ha -1 in pots using normal and acidified irrigation water under Al Zaid and Al Semaih soils in evaporative cooled greenhouse conditions. Total dry matter (TDM) accumulation and nutrients uptake had positive relation while soil pH showed negative correlation with TDM and uptake availability of all nutrients. Addition of S 0 at the rate of 5 t ha -1 combined with N fertilizer recorded improved NUE, superior TDM and maximum uptake of all nutrients under both types of irrigation water and soils. Collectively, the results indicate that S fertilization is required to improve NUE and thereby maintaining a sufficient availability of nutrients and growth of corn in sandy calcareous soil.